Green Energy Based Coupled Inductor Interleaved Converter with MPPT Technique for BLDC Application - V. Senthil Nayagam; L. Premalatha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents a high step-up converter with combination of battery and solar energy source application. The proposed green energy source boosted by using coupled inductor interleaved converter. The coupled inductor and voltage double circuit can reach the high voltage gain without more stress on the converter circuit as well as muchchanges in duty cycle. The photo voltaic system maximum output is 12volts it can be varied by changes of irradiation level .The maximum output voltage is tracking by using MPPT and supplies to the coupled inductor interleaved boost converter. The MPPT working based on the P & O algorithm .The output level of the photo voltaic is high then the battery is charging as well as BLDC motor also being driven efficiently.Whenever the irradiation level will be low the output level of the photo voltaic is less than the battery will be charging and then the motor will running by battery power.